2005
DOI: 10.1517/14656566.6.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Novel effects other than antisecretory action and off-label use of proton pump inhibitors

Abstract: The proton pump inhibitors (PPIs) are a relatively new class of agents used for the treatment of acid-related disorders, including peptic ulcer diseases, reflux oesophagitis and Zollinger-Ellison syndrome, and in enhancing antibiotic therapy in the eradication of Helicobacter pylori in patients with peptic ulcer disease. The PPIs are the most potent gastric acid-suppressing agents currently in clinical use. According to the recent basic study, PPIs may act not only as potent acid suppressants, but also as anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…The reason for PPI responsiveness of this condition is not completely understood but could be due to other, non-antisecretory effects of PPIs [118], of which the anti-inflammatory action [119] is the most relevant one. In vitro and in vivo studies suggest that the anti-inflammatory effects of PPI therapy rather than acid suppression alone may be responsible for this improvement through inhibition of the Th2-allergic pathway [120].…”
Section: Resultsmentioning
confidence: 99%
“…The reason for PPI responsiveness of this condition is not completely understood but could be due to other, non-antisecretory effects of PPIs [118], of which the anti-inflammatory action [119] is the most relevant one. In vitro and in vivo studies suggest that the anti-inflammatory effects of PPI therapy rather than acid suppression alone may be responsible for this improvement through inhibition of the Th2-allergic pathway [120].…”
Section: Resultsmentioning
confidence: 99%
“…We chose PPI's because they are known to be widely used off-label in high volumes of patients and patient are often sent home on a PPI based on off-label use [12]. We chose IVIG and Factor VIIa in part because they are very costly, but also because they were thought to be prescribed for a variety of off-label indications [13].…”
Section: Methodsmentioning
confidence: 99%
“…The use of histamine type 2 receptor (H2R) antagonists and protonpump inhibitors (PPIs) has become widespread for the treatment of peptic ulcer disease and gastroesophageal reflux disease. 1 Although the influence of long-term acid suppression is controversial in the stomach, some reports indicated that usage of PPIs has known to be associated with the formation of gastric sporadic fundic gland polyps 2,3 and hyperplastic polyps. 4 In addition, there are reports indicating that long-term usage of H2R antagonists or PPI may facilitate the formation of gastric malignant lesions such as gastric carcinoid tumors and cancers.…”
Section: Introductionmentioning
confidence: 99%